2000
DOI: 10.1021/ac000469c
|View full text |Cite
|
Sign up to set email alerts
|

Short-Wave Near-Infrared Spectroscopy of Biological Fluids. 1. Quantitative Analysis of Fat, Protein, and Lactose in Raw Milk by Partial Least-Squares Regression and Band Assignment

Abstract: The present study has aimed at providing new insight into short-wave near-infrared (NIR) spectroscopy of biological fluids. To do that, we analyzed NIR spectra in the 800-1,100-nm region of 100 raw milk samples. The contents of fat, proteins, and lactose were predicted by partial least-squares (PLS) regression and band assignment in that region was investigated based upon PLS loading plots and regression coefficients. For the fat prediction, the whole set of samples was divided into two groups and the fat conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(75 citation statements)
references
References 19 publications
2
73
0
Order By: Relevance
“…rapidity, non-destructive sample analysis and, especially, a great potential for on-line analysis (RU & gLATZ, 2000;ALBANELL et al, 2003). FT NIR method has been used to measure the content of various constituents in homogenised cow milk (SATO et al, 1987;RODRIgUEZ-OTERO, HERMIDA & CENTENO, 1997;RU & gLATZ, 2000;ŠAŠIČ & OZAKI, 2001). A few authors have reported analysis of non-homogenised milk samples (CHEN, IyO & KAWANO, 1999;LAPORTE & PAQUIN, 1999).…”
mentioning
confidence: 99%
“…rapidity, non-destructive sample analysis and, especially, a great potential for on-line analysis (RU & gLATZ, 2000;ALBANELL et al, 2003). FT NIR method has been used to measure the content of various constituents in homogenised cow milk (SATO et al, 1987;RODRIgUEZ-OTERO, HERMIDA & CENTENO, 1997;RU & gLATZ, 2000;ŠAŠIČ & OZAKI, 2001). A few authors have reported analysis of non-homogenised milk samples (CHEN, IyO & KAWANO, 1999;LAPORTE & PAQUIN, 1999).…”
mentioning
confidence: 99%
“…Sašić and Ozaki [180] subjected raw milk to SW-NIR (800-1100 nm) measurements. They predicted the fat, protein, and lactose contents using PLS regression and band assignment.…”
Section: B121 Milksmentioning
confidence: 99%
“…Therefore, rapid and simple analytical techniques to implement the discrimination tasks are highly demanding. Near infrared (NIR) spectroscopy, as a rapid, simple, nondestructive, and environmentally friendly technique, has been proven to be a well alternative to the wet chemical tools; examples of which are associated with its extensive applications in agricultural [8], manufacturing [9], pharmaceutical [10], and food industries [11][12][13].…”
Section: Introductionmentioning
confidence: 99%